Perencanaan dan Peningkatan Kinerja Organisasi - Dina Maulidatul Hasanah; Firda Dwi Damayanti; Moh. Zakariya Fahlevi; Mu’alimin Mu’alimin (Pusat Riset dan Inovasi Nasional, 2025)
Planning and improving organizational performance is a crucial aspect in addressing the increasingly complex dynamics of business competition. This study aims to analyze the factors influencing organizational performance and effective planning strategies to enhance it. The method used is a literature review by analyzing 9 selected journal articles from 20 relevant references. The results show that organizational performance is influenced by several key factors, including human resource management, organizational structure, and financial aspects. Moreover, holistic, adaptive, and integrated strategic planning—combined with innovation and organizational learning—has proven to be significant in improving performance. This study also identified a research gap, specifically the lack of integration between strategic planning and external factors such as changes in the business environment. The practical implications highlight the importance of adopting a data-driven approach, involving all stakeholders, and implementing a continuous performance management cycle (planning, monitoring, reviewing, and rewarding). These findings contribute to the development of performance management theory and organizational practices in achieving strategic objectives.